Orthogonalizing Boolean Subtraction of Minterms or Ternary-Vectors - Can, Yavuz; Fischer, Georg (Acta Physica Polonica A, 2015)
In this paper, a method called “Boolean subtraction” which enables the subtraction of two minterms and of two functions of the disjunctive normal form respectively of two ternary-vectors and of two ternary-vector-lists is presented. The advantage of “Boolean subtraction” is that the calculated results are already presented in an orthogonal form, which has a significant advantage for further calculations. It replaces two procedures, once building the difference and then the subsequent orthogonalizing and has faster computing time in comparison. Furthermore, another equation is developed from the property of this new method providing orthogonal results in order to orthogonalize functions of the disjunctive normal for
Keywords: Set Theory; Difference Building; Ternary-Vector; K-map; Venn-Diagram; Computation Time; Orthogonality